Two problems on varieties of groups generated by wreath products - Vahagn H. Mikaelian (International Journal of Mathematics and Mathematical Sciences)
We outline results on varieties of groups generated by Cartesian and direct wreath products of abelian groups and pose two problems related to our recent results in that direction. A few related topics are also considered.